2014
DOI: 10.1111/nan.12054
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of synaptic vesicle protein 2 (SV2) isoforms in patients with temporal lobe epilepsy and hippocampal sclerosis

Abstract: In classical MTS1A, the expression of SV2 isoforms is altered with a marked decrease of SV2A and SV2B paralleling synaptic loss and a selective increase of SV2C in sprouting mossy fibres. These findings suggest a different physiology of sprouting synapses and the possibility to target them with SV2C-specific strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
54
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 43 publications
13
54
2
Order By: Relevance
“…In general, changes in synaptic proteins might parallel synaptic loss or formation (Crevecoeur et al, 2013). For example, in sclerotic hippocampus of TLE patients VGLUT-1 expression has been found to be down-regulated in regions with severe neuronal loss, but strongly up-regulated in regions characterized by formation of new glutamaregic synapses (i.e.…”
Section: The Glutamate/gaba Hypothesis: Enhancement Of Excitation mentioning
confidence: 99%
“…In general, changes in synaptic proteins might parallel synaptic loss or formation (Crevecoeur et al, 2013). For example, in sclerotic hippocampus of TLE patients VGLUT-1 expression has been found to be down-regulated in regions with severe neuronal loss, but strongly up-regulated in regions characterized by formation of new glutamaregic synapses (i.e.…”
Section: The Glutamate/gaba Hypothesis: Enhancement Of Excitation mentioning
confidence: 99%
“…SV2A is homogeneously distributed in the rodent brain (7), whereas other isoforms have discrete distributions suggesting specific functional roles (8). Reduced expression of SV2A and SV2B in areas of synaptic loss in temporal lobe epilepsy and a selective increase in SV2C expression in sprouting mossy fibers in mesial temporal sclerosis have been reported (4), further indicating a role for SV2 in epilepsy and related neurodegeneration. 19 F-UCB-H is a novel ligand with a nanomolar affinity for SV2A and an in silico, in vitro, and in vivo ADME (absorption, distribution, metabolism, and excretion) profile that makes it suitable for consideration as a candidate SV2A PET ligand (10).…”
mentioning
confidence: 98%
“…Although the role of some SV proteins has been studied in great detail and their function is generally understood (1,2), other SV proteins require further study. The potential value of SV protein 2 (SV2) isoforms (3)(4)(5) as drug targets has renewed interest in these proteins. The antiepileptic drug levetiracetam (LEV) binds to SV2A (6), suggesting a role for SV2A in the pathology underlying certain forms of epilepsy.…”
mentioning
confidence: 99%
“…Synaptic vesicle protein 2 (SV2) is a neuronal vesicle membrane glycoprotein that appears to be an important target in treatment of partial and generalized epilepsies [6]. It is thought to decrease neuronal excitability [7] since knockout of synaptic vesicle protein 2A (SV2A) in mice leads to seizures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression of SV2A is reduced during epileptogenesis in the rat, and changes in expression of SV2A may have consequences for progression of epilepsy [8]. Recent studies have found downregulation of SV2A expression in brain tissue obtained from patients with intractable temporal lobe epilepsy [6,9]. Several lines of evidence suggest that SV2A is the binding site for the antiepileptic drug levetiracetam (LEV) [10,11].…”
Section: Introductionmentioning
confidence: 99%